lab07_sol_su09

lab07_sol_su09 - ECE 220, Section 051 Problem Lab Number 7...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ECE 220, Section 051 Problem Lab Number 7 Solution Chapter 8, Laplace Transforms Part I. Fundamental Properties of Laplace Transforms 1. Use the basic definition of the Laplace transform to evaluate: f ( t ) = e- a ( t- t 1 ) u ( t- t 1 ) Check using Laplace transform properties. Solution:(Using Basic Definition) F ( s ) = f ( t ) e- st dt = e- a ( t- t 1 ) u ( t- t 1 ) e- st dt F ( s ) = e at 1 t 1 e- t ( a + s ) dt = e at 1- ( s + a ) e- t ( s + a ) t 1 F ( s ) = e at 1- ( s + a )- e- t 1 ( s + a ) = e at 1- st 1- at 1 s + a = e- st 1 s + a Solution:(Using Laplace Transform Properties) f ( t ) = e- a ( t- t 1 ) u ( t- t 1 ) = g ( t- t 1 ) Now, g ( t ) = e- at u ( t ) So, G ( s ) = 1 s + a As f ( t ) = g ( t- t 1 ), F ( s ) = e- st 1 s + a 2. Use the basic definition of the Laplace transform to show that: L [ f ( t- a ) u ( t- a )] = F ( s ) e- as where F ( s ) = L [ f ( t )] Check using Laplace transform properties. Solution:(Using Basic Definition) H ( s ) = h ( t ) e- st dt = f ( t- a ) u ( t- a ) e- st dt H ( s ) = a f ( t- a ) e- st e- at e at dt = a f ( t- a ) e- st e- as e as dt H ( s ) = e- as a f ( t- a ) e- s ( t- a ) dt = e- as f ( t ) e- s ( t ) dt = e- as F ( s ) 1 Solution:(Using Laplace Transform Properties) h ( t ) = f ( t- a ) u ( t- a ) = g ( t- a ) Now, g ( t ) = f ( t ) u ( t ) So, H ( s ) = e- as G ( s ) H ( s ) = e- as F ( s ) 3. Use the basic definition of the Laplace transform to show that: L [ e- at f ( t )] = F ( s + a ) where F ( s ) = L [ f ( t )] Solution:(Using Basic Definition) H ( s ) = h ( t ) e- st dt = e- at f ( t ) e- st dt H ( s ) = a f ( t ) e- t ( s + a ) dt = f ( t ) e- t ( s + a ) dt H ( s ) = F ( s + a ) 4. Use the results from the above problems to evaluate the Laplace transform of: (a) e- at cos( t ) Solution: s- a ( s- a ) 2 + 2 (b) e- at sin( t ) Solution: ( s- a ) 2 + 2 using the known transform pairs...
View Full Document

Page1 / 8

lab07_sol_su09 - ECE 220, Section 051 Problem Lab Number 7...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online